Optimization of glass transition temperature and pot life of epoxy blends using response surface methodology (RSM) - Ramli, Junid; Siregar, J. P.; Nor Azam, Endot; Jeefferie, Abd Razak; Wilkinson, Arthur N. (MDPI, 2021)
The aim of this work was to improve the processability of triglycidyl-p-aminophenol (TGPAP) epoxy resin. To achieve this improvement, a diluent, the diglycidyl ether of bisphenol F (DGEBF or BPF), was added to TGPAP, and the blended epoxy was then cured with 4, 4′-diaminodiphenyl sulfones (DDS). A response surface methodology (RSM) was used, with the target response being to achieve a blended resin with a high glass transition temperature (Tg) and maximum pot life (or processing window, PW). Characterization through dynamic mechanical thermal analysis (DMTA) and using a rheometer indicated that the optimum formulation was obtained at 55.6 wt.% of BPF and a stoichiometric ratio of 0.60. Both values were predicted to give Tg at 180 °C and a processing window of up to 136.1 min. The predicted values were verified, with the obtained Tg and processing window (PW) being 181.2 ± 0.8 °C and 140 min, respectively, which is close to the values predicted using the RSM.